INTERNET USAGE BY COLLEGE STUDENTS AS THE SEARCHING MEDIA AND INFORMATION INVESTIGATION - Iman Murtono Soenhadji; Romdhoni Susiloatmadja (Universitas Gunadarma, 2009)
This research aims to investigate internet utilization among undergraduate students (S1) of Information Systems, Information Technology, Management, Accounting and D3 degree students of Business and Entrepreneurship. Extant internet facility in this study is utilization of University website by the students in accordance with their academic grades and assignments given by the lecturers. This research also focuses on determinant and constraint factors in choosing internet as media for information searching and browsing. The respondents for this study are students of Faculty of Economics and Faculty of Computer Science, Gunadarma University. From 1200 targeted respondents, only 41 students respond in the first stage and 140 in the second stage. Questionnaire is delivered using (download mode in) lecturer website. Respondents were grouped based on the study program, Statistical testing using SPSS indicates that the most frequent visited websites are education-related ones, whereas the most searched and browsed websites are the commercial and institutional ones. The most exploited menu in the University website is Studentsite. Pearson’s chi-square test (with significance degree = 0.006) denotes a significant relationship between study program and students’ confidence level of internet contribution to their study. Moreover, the levels of students’ confidence vary among program studies. Keywords: determinant factors, constraint factors, internet, information, university students, websites.